Laser engraving PBT material for keycaps and preparation method thereof
By adding specific components to the keycap material and using the twin screw extrusion process, the problems of poor fluidity and mist flow patterns of the keycap material are solved, the laser engraving effect and wear resistance are improved, and the performance improvement of the keycap product is achieved .
Patent Information
- Application Number
- CN202111579754.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-22
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2041-12-22
AI Technical Summary
The existing keycap materials have poor fluidity, and the surface of the product is prone to mist flow, and the handwriting is not clear enough after laser engraving, and the traditional printing method is not environmentally friendly and easy to wear.
Using radium engraved PBT material, styrene-acrylonitrile copolymer, polymethyl methacrylate, chopped glass fiber, gamma-(2,3-epoxypropoxy)propyltrimethoxysilane, oily black and Specific antioxidants, processed by premix and twin screw extruders, improve material flowability and mechanical properties, improve compatibility and surface hardness.
The obtained material has good fluidity, a flat surface, wear-resistant, and does not shine after friction. It has good impact and tensile strength. It is suitable for keyboard keycaps, and the handwriting is clearer after laser engraving and has increased service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of C08L67 / 02, and in particular to a laser-engraved PBT material for a keycap and a preparation method thereof. Background Art
[0002] Most keyboard keycaps are made of PBT resin, ABS resin, PC resin, etc. PBT resin has become a popular material for keycaps due to its excellent resistance to solvents, acids and alkalis. However, pure PBT material has poor fluidity, and the surface of the finished product is prone to misty flow lines, which affects the properties of the finished product and also affects the sales of the finished product. In addition, the fonts on traditional keycaps are printed, which is not only not environmentally friendly but also easy to wear off during the use of the keycaps. In order to change this phenomenon, laser engraving technology has emerged, but ordinary PBT products are not clear enough after laser engraving, and the engraving effect is not ideal.
[0003] Chinese patent CN112852119A discloses a material suitable for mechanical keyboard keycaps made of polycarbonate, PBT resin, glass fiber, and hyperbranched polyester, which has good fluidity and low warping effect. Chinese patent CN109880276A discloses a composite material suitable for two-color keycaps made of PBT resin and ABS resin as the main materials, which has high mechanical strength, good wear resistance, and anti-greasy effect. This application proposes a laser-engraved PBT material for keycaps, which has clear laser-engraved characters, good product fluidity, a smooth and wear-resistant surface, and a non-shiny surface after friction. Summary of the invention
[0004] The first aspect of the present invention proposes a laser-engraved PBT material for keycaps, characterized in that the raw materials for preparation include, by weight, 70-90 parts of thermoplastic polymer, 5-15 parts of glass fiber, 1-5 parts of compatibilizer, 0.1-1.5 parts of synergist, and 0-2 parts of oil black.
[0005] In a preferred embodiment, the raw materials for preparation include, by weight, 80-90 parts of thermoplastic polymer, 5-10 parts of glass fiber, 1-3 parts of compatibilizer, 0.1-1 parts of synergist, and 1.5-2 parts of oil black.
[0006] In a preferred embodiment, the raw materials for preparation include, by weight, 84 parts of thermoplastic polymer, 10 parts of glass fiber, 3 parts of compatibilizer, 1 part of synergist, and 2 parts of oil black.
[0007] In a preferred embodiment, the thermoplastic polymer includes polybutylene terephthalate; the thermoplastic polymer also includes at least one of styrene-acrylonitrile copolymer, polystyrene, polymethyl methacrylate, ABS resin, and impact polystyrene.
[0008] In a preferred embodiment, the thermoplastic polymer is a compound of polybutylene terephthalate, styrene-acrylonitrile copolymer and polymethyl methacrylate.
[0009] In a preferred embodiment, the mass ratio of polybutylene terephthalate, styrene-acrylonitrile copolymer and polymethyl methacrylate is (4-5): (1-3): (1-3). Preferably, the mass ratio of polybutylene terephthalate, styrene-acrylonitrile copolymer and polymethyl methacrylate is 4.9:2:1.5.
[0010] In a preferred embodiment, the polybutylene terephthalate has a melt index of 40-60 g / 10 min at 250° C., and more preferably, the polybutylene terephthalate has a melt index of 42-55 g / 10 min at 250° C.
[0011] In a preferred embodiment, the glass fiber is a chopped glass fiber. Preferably, the monofilament diameter of the chopped glass fiber is 9-13 μm, and the length of the chopped glass fiber is 3-4 mm.
[0012] In a preferred embodiment, the compatibilizer is at least one of styrene-maleic anhydride copolymer, maleic anhydride derivatives, methyl methacrylate-butadiene-styrene terpolymer, and polydimethylolpropionic acid derivatives.
[0013] In a preferred embodiment, the compatibilizer is styrene-maleic anhydride copolymer.
[0014] In a preferred embodiment, the synergistic aid is selected from at least one of a coupling agent, a lubricant, an antioxidant, a flame retardant, a scratch resistant agent, a wear resistant agent, and an antibacterial agent.
[0015] In a preferred embodiment, the synergistic aid is a coupling agent, a lubricant, or an antioxidant.
[0016] In a preferred embodiment, the mass ratio of the coupling agent, the lubricant and the antioxidant is (3-5):3:(1-3), and more preferably, the mass ratio of the coupling agent, the lubricant and the antioxidant is 4:3:3.
[0017] In a preferred embodiment, the coupling agent is selected from at least one of a titanate coupling agent, a silane coupling agent, an aluminate coupling agent, and a zirconate coupling agent. Preferably, the coupling agent is a silane coupling agent.
[0018] In a preferred embodiment, the silane coupling agent is selected from at least one of epoxy silane coupling agent, amino silane coupling agent, methacryl silane coupling agent, isocyanate silane coupling agent, and piperazine silane coupling agent. Preferably, the silane coupling agent is epoxy silane coupling agent.
[0019] In a preferred embodiment, the epoxy silane coupling agent is selected from at least one of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. More preferably, the epoxy silane coupling agent is γ-(2,3-epoxypropyloxy)propyltrimethoxysilane.
[0020] In a preferred embodiment, the lubricant is selected from at least one of metal stearate, glyceryl stearate, polyolefin wax, pentaerythritol stearate, ethylene bisstearamide, acrylic acid ethylene copolymer wax, and polyol wax ester.
[0021] In a preferred embodiment, the lubricant is pentaerythritol stearate.
[0022] In a preferred embodiment, the antioxidant is a compound substance of antioxidant 1010 and antioxidant 168. Preferably, the mass ratio of antioxidant 1010 to antioxidant 168 is 2:1.
[0023] In a preferred embodiment, the pigment is selected from at least one of carbon black and oil black, preferably, the pigment is oil black. The oil black is purchased from any manufacturer, preferably, it is purchased from Sumitomo Black H3B of Japan.
[0024] The applicant found that adding styrene-acrylonitrile copolymer and polymethyl methacrylate can improve the fluidity of the material and increase the scratch resistance of the product. At the same time, adding specific short glass fibers further improves the mechanical properties of the product. However, the applicant found that the compatibility between the main materials used in this application is poor, and material dissolution and stratification are prone to occur between resins and between resins and short glass fibers, resulting in flow lines on the surface of the product. The applicant accidentally found that adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, oil black, styrene-maleic anhydride copolymer, specific antioxidants and other raw materials can improve the compatibility problem and further improve the mechanical properties and surface hardness of the product. The applicant speculates that the possible reason is that the compounding of specific antioxidants improves the thermal stability of the resin in the high temperature zone of the extruder, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane improves the bonding between glass fibers and resins, further improves the thermal stability of the resin, reduces the phenomenon of flow lines on the surface of the product, and also improves the tensile strength, impact strength and other mechanical properties of the product.
[0025] The second aspect of the present invention provides a method for preparing a laser-engraved PBT material for a keycap, comprising the following steps:
[0026] (1) Air drying of thermoplastic polymers;
[0027] (2) Pour the dried thermoplastic polymer, compatibilizer, synergist and pigment into a high-speed mixer for premixing;
[0028] (3) Add the premixed materials into the hopper of the twin-screw extruder, add glass fiber, and carry out melt mixing, extrusion, cooling, drying, pelletizing, and packaging.
[0029] In a preferred embodiment, the temperature of the forced air drying in step (1) is 80-140° C., and the drying time is 2-4 hours.
[0030] In a preferred embodiment, the temperatures of each section in the twin-screw extruder in step (3) are set as follows: section one 100°C, section two 245°C, section three 250°C, section four 245°C, section five 240°C, section six 230°C, section seven 205°C, section eight 190°C, and the die temperature is 230°C.
[0031] In a preferred embodiment, the output of the twin-screw extruder is 350 kg / H.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The PBT material obtained by the present invention has good fluidity, and the surface of the product is not prone to produce mist-like flow lines. The prepared keycap has good wear resistance, the surface is not shiny after friction, and has good impact resistance and tensile strength and other mechanical properties, and is particularly suitable for producing keyboard keycaps.
[0034] 2. The PBT material obtained by the present invention adds oil black as a pigment, which ensures the blackness of the product while improving the clarity and whiteness of the writing after laser engraving of the product, thereby increasing the service life of the product. DETAILED DESCRIPTION
[0035] Example 1
[0036] The first aspect of this embodiment proposes a laser engraving PBT material for keycaps. The raw materials for preparation include, by weight: 49 parts of polybutylene terephthalate, 20 parts of styrene-acrylonitrile copolymer, 15 parts of polymethyl methacrylate, 10 parts of glass fiber, 3 parts of styrene-maleic anhydride copolymer, 0.4 parts of coupling agent KH560, 0.3 parts of pentaerythritol stearate, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 2 parts of oil black.
[0037] Polybutylene terephthalate was purchased from Changchun, Taiwan, China, with a brand number of 1200-211M.
[0038] The melt index of styrene-acrylonitrile copolymer was 5 g / 10 min (200°C / 5 kg), purchased from Chi Mei in Taiwan, China, with the model number being PN-117C.
[0039] The melt index of polymethyl methacrylate is 16 g / 10 min (ASTM D-1238), and it was purchased from Chi Mei in Taiwan, China, with a model number of CM211.
[0040] The glass fiber has a monofilament diameter of 9-13 μm and a length of 3 mm. It was purchased from Chongqing International Composite Materials Co., Ltd. and its model is 303H.
[0041] The oil-based black was purchased from Japan's Sumitomo Black H3B.
[0042] The second aspect of this embodiment provides a method for preparing a laser-engraved PBT material for a keycap, comprising the following steps:
[0043] (1) drying polybutylene terephthalate by air blast at 140° C. for 3 to 4 hours, and drying styrene-acrylonitrile copolymer and polymethyl methacrylate by air blast at 80° C. for 2 to 4 hours respectively;
[0044] (2) Pour the dried polybutylene terephthalate, styrene-acrylonitrile copolymer, polymethyl methacrylate, styrene-maleic anhydride copolymer, coupling agent KH560, pentaerythritol stearate, antioxidant 1010, antioxidant 168 and oil black into a high-speed mixer for premixing;
[0045] (3) Add the premixed materials into the hopper of the twin-screw extruder and feed the glass fiber into the side feeder; perform melt mixing, extrusion, cooling, drying, pelletizing and packaging.
[0046] In step (3), the temperatures of each section of the twin-screw extruder are set to 100°C for the first section, 245°C for the second section, 250°C for the third section, 245°C for the fourth section, 240°C for the fifth section, 230°C for the sixth section, 205°C for the seventh section, 190°C for the eighth section, and the die head temperature is 230°C.
[0047] Example 2
[0048] The first aspect of this embodiment proposes a laser engraving PBT material for keycaps. The raw materials for preparation include, by weight: 44 parts of polybutylene terephthalate, 10 parts of styrene-acrylonitrile copolymer, 30 parts of polymethyl methacrylate, 10 parts of glass fiber, 3 parts of styrene-maleic anhydride copolymer, 0.4 parts of coupling agent KH560, 0.3 parts of pentaerythritol stearate, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 2 parts of oil black.
[0049] Polybutylene terephthalate was purchased from Changchun, Taiwan, China, with a brand number of 1200-211M.
[0050] The melt index of styrene-acrylonitrile copolymer was 5 g / 10 min (200°C / 5 kg), purchased from Chi Mei in Taiwan, China, with the model number being PN-117C.
[0051] The melt index of polymethyl methacrylate is 16 g / 10 min (ASTM D-1238), and it was purchased from Chi Mei in Taiwan, China, with a model number of CM211.
[0052] The glass fiber has a monofilament diameter of 9-13 μm and a length of 3 mm. It was purchased from Chongqing International Composite Materials Co., Ltd. and its model is 303H.
[0053] The oil-based black was purchased from Japan's Sumitomo Black H3B.
[0054] The second aspect of this embodiment provides a method for preparing a laser-engraved PBT material for a keycap, comprising the following steps:
[0055] (1) drying polybutylene terephthalate by air blast at 140° C. for 3 to 4 hours, and drying styrene-acrylonitrile copolymer and polymethyl methacrylate by air blast at 80° C. for 2 to 4 hours respectively;
[0056] (2) Pour the dried polybutylene terephthalate, styrene-acrylonitrile copolymer, polymethyl methacrylate, styrene-maleic anhydride copolymer, coupling agent KH560, pentaerythritol stearate, antioxidant 1010, antioxidant 168 and oil black into a high-speed mixer for premixing;
[0057] (3) Add the premixed materials into the hopper of the twin-screw extruder and feed the glass fiber into the side feeder; perform melt mixing, extrusion, cooling, drying, pelletizing and packaging.
[0058] In step (3), the temperatures of each section of the twin-screw extruder are set to 100°C for the first section, 245°C for the second section, 250°C for the third section, 245°C for the fourth section, 240°C for the fifth section, 230°C for the sixth section, 205°C for the seventh section, 190°C for the eighth section, and the die head temperature is 230°C.
[0059] Example 3
[0060] The first aspect of this embodiment proposes a laser engraving PBT material for keycaps. The raw materials for preparation include, by weight: 44 parts of polybutylene terephthalate, 30 parts of styrene-acrylonitrile copolymer, 10 parts of polymethyl methacrylate, 10 parts of glass fiber, 3 parts of styrene-maleic anhydride copolymer, 0.4 parts of coupling agent KH560, 0.3 parts of pentaerythritol stearate, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 2 parts of oil black.
[0061] Polybutylene terephthalate was purchased from Changchun, Taiwan, China, with a brand number of 1200-211M.
[0062] The melt index of styrene-acrylonitrile copolymer was 5 g / 10 min (200°C / 5 kg), purchased from Chi Mei in Taiwan, China, with the model number being PN-117C.
[0063] The melt index of polymethyl methacrylate is 16 g / 10 min (ASTM D-1238), and it was purchased from Chi Mei in Taiwan, China, with a model number of CM211.
[0064] The glass fiber has a monofilament diameter of 9-13 μm and a length of 3 mm. It was purchased from Chongqing International Composite Materials Co., Ltd. and its model is 303H.
[0065] The oil-based black was purchased from Japan's Sumitomo Black H3B.
[0066] The second aspect of this embodiment provides a method for preparing a laser-engraved PBT material for a keycap, comprising the following steps:
[0067] (1) drying polybutylene terephthalate by air blast at 140° C. for 3 to 4 hours, and drying styrene-acrylonitrile copolymer and polymethyl methacrylate by air blast at 80° C. for 2 to 4 hours respectively;
[0068] (2) Pour the dried polybutylene terephthalate, styrene-acrylonitrile copolymer, polymethyl methacrylate, styrene-maleic anhydride copolymer, coupling agent KH560, pentaerythritol stearate, antioxidant 1010, antioxidant 168 and oil black into a high-speed mixer for premixing;
[0069] (3) Add the premixed materials into the hopper of the twin-screw extruder and feed the glass fiber into the side feeder; perform melt mixing, extrusion, cooling, drying, pelletizing and packaging.
[0070] In step (3), the temperatures of each section of the twin-screw extruder are set to 100°C for the first section, 245°C for the second section, 250°C for the third section, 245°C for the fourth section, 240°C for the fifth section, 230°C for the sixth section, 205°C for the seventh section, 190°C for the eighth section, and the die head temperature is 230°C.
[0071] Example 4
[0072] The first aspect of this embodiment proposes a laser-engraved PBT material for keycaps. The raw materials for preparation include, by weight: 49 parts of polybutylene terephthalate, 20 parts of styrene-acrylonitrile copolymer, 15 parts of polymethyl methacrylate, 10 parts of glass fiber, 3 parts of styrene-maleic anhydride copolymer, 0.4 parts of coupling agent KH560, 0.3 parts of pentaerythritol stearate, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 2 parts of carbon black.
[0073] Polybutylene terephthalate was purchased from Changchun, Taiwan, China, with a brand number of 1200-211M.
[0074] The melt index of styrene-acrylonitrile copolymer was 5 g / 10 min (200°C / 5 kg), purchased from Chi Mei in Taiwan, China, with the model number being PN-117C.
[0075] The melt index of polymethyl methacrylate is 16 g / 10 min (ASTM D-1238), and it was purchased from Chi Mei in Taiwan, China, with a model number of CM211.
[0076] The glass fiber has a monofilament diameter of 9-13 μm and a length of 3 mm. It was purchased from Chongqing International Composite Materials Co., Ltd. and its model is 303H.
[0077] Carbon black was purchased from Mitsubishi of Japan, model 50#.
[0078] The second aspect of this embodiment provides a method for preparing a laser-engraved PBT material for a keycap, comprising the following steps:
[0079] (1) drying polybutylene terephthalate by air blast at 140° C. for 3 to 4 hours, and drying styrene-acrylonitrile copolymer and polymethyl methacrylate by air blast at 80° C. for 2 to 4 hours respectively;
[0080] (2) Pour the dried polybutylene terephthalate, styrene-acrylonitrile copolymer, polymethyl methacrylate, styrene-maleic anhydride copolymer, coupling agent KH560, pentaerythritol stearate, antioxidant 1010, antioxidant 168 and carbon black into a high-speed mixer for premixing;
[0081] (3) Add the premixed materials into the hopper of the twin-screw extruder and feed the glass fiber into the side feeder; perform melt mixing, extrusion, cooling, drying, pelletizing and packaging.
[0082] In step (3), the temperatures of each section of the twin-screw extruder are set to 100°C for the first section, 245°C for the second section, 250°C for the third section, 245°C for the fourth section, 240°C for the fifth section, 230°C for the sixth section, 205°C for the seventh section, 190°C for the eighth section, and the die head temperature is 230°C.
[0083] Performance Testing
[0084] The mechanical properties and laser engraving performance of the product prepared in the example were tested, and the test results are recorded in Table 1.
[0085] Table 1
[0086]
Claims
1. A laser engraved PBT material for keycaps, characterized in that: The raw materials for preparation are calculated by weight, including: 44 parts of polybutylene terephthalate, 30 parts of styrene-acrylonitrile copolymer, 10 parts of polymethyl methacrylate, 10 parts of glass fiber, 3 parts of styrene-maleic anhydride copolymer, 0.4 parts of coupling agent KH560, 0.3 parts of pentaerythritol stearate, 0.2 parts of antioxidant 1010, 0.1 parts of antioxidant 168, and 2 parts of oil black; The melt index of styrene-acrylonitrile copolymer is 5 g / 10 min, 200 °C / 5 kg; The melt index of polymethyl methacrylate is 16 g / 10 min, ASTM D-1238; The monofilament diameter of glass fiber is 9-13 μm and the length is 3 mm; Oil black was purchased from Japan's Sumitomo BlackH3B; The method for preparing the laser-engraved PBT material for keycaps comprises the following steps: (1) drying polybutylene terephthalate by air blast at 140° C. for 3 to 4 hours, and drying styrene-acrylonitrile copolymer and polymethyl methacrylate by air blast at 80° C. for 2 to 4 hours respectively; (2) Pour the dried polybutylene terephthalate, styrene-acrylonitrile copolymer, polymethyl methacrylate, styrene-maleic anhydride copolymer, coupling agent KH560, pentaerythritol stearate, antioxidant 1010, antioxidant 168 and oil black into a high-speed mixer for premixing; (3) adding the premixed materials into the hopper of a twin-screw extruder, adding glass fiber, and performing melt mixing, extrusion, cooling, drying, pelletizing, and packaging; In the step (3), the temperature of each section in the twin-screw extruder is set as follows: 100°C for the first section, 245°C for the second section, 250°C for the third section, 245°C for the fourth section, 240°C for the fifth section, 230°C for the sixth section, 205°C for the seventh section, 190°C for the eighth section, and the die head temperature is 230°C.
2. A method for preparing the laser-engraved PBT material for keycaps according to claim 1, characterized in that: The following steps are involved: (1) drying polybutylene terephthalate by air blast at 140° C. for 3 to 4 hours, and drying styrene-acrylonitrile copolymer and polymethyl methacrylate by air blast at 80° C. for 2 to 4 hours respectively; (2) Pour the dried polybutylene terephthalate, styrene-acrylonitrile copolymer, polymethyl methacrylate, styrene-maleic anhydride copolymer, coupling agent KH560, pentaerythritol stearate, antioxidant 1010, antioxidant 168 and oil black into a high-speed mixer for premixing; (3) Add the premixed materials into the hopper of a twin-screw extruder, add glass fiber, and perform melt mixing, extrusion, cooling, drying, pelletizing, and packaging.
Citation Information
Cited By
Highly antibacterial sanitary keycap material and preparation method thereof
CN116694044A